Micromechanical analysis of high fibre volume fraction polymeric laminates using micrograph-based representative volume element models. (20th October 2022) - Kempesis, D.; Iannucci, L.; Ramesh, K.T.; Del Rosso, S.; Curtis, P.T.; Pope, D.; Duke, P.W.
Abstract: This work develops RVE-based finite element (FE) models to understand how the microstructure of Ultra-High-Molecular-Weight Polyethylene (UHMWPE) composites affects the overall mechanical behaviour of the laminate. The models represent a [0/90] configuration with a random fibre packing sequence through the thickness of each ply, as well as a variation in the cross-sectional shape of the fibres, both obtained from laminate cross section micrograph images. The uncertainty of interface properties and its effects on the overall mechanical response is also investigated. The response of the fibre is assumed to be viscoelastic-plastic and transversely isotropic and the three-dimensional constitutive behaviour is implemented through a user-defined subroutine in the LS-DYNA explicit FE code. Constituent properties are calibrated using experimental results on UHMWPE single fibres and a generic thermoplastic polyurethane resin material. The numerical results generated by the RVE models are validated against experimental results found in the open literature. Special focus was given to the in-plane shear and out-of-plane compression response of UHMWPE laminates. Our results can be used as inputs in a homogenised continuum level model, to express the effect of uncertainties which propagate from the microstructure to the macro-scale response. Graphical abstract: Image 1